2016
DOI: 10.2807/1560-7917.es.2016.21.39.30353
|View full text |Cite
|
Sign up to set email alerts
|

A norovirus intervariant GII.4 recombinant in Victoria, Australia, June 2016: the next epidemic variant?

Abstract: A norovirus recombinant GII.P4_NewOrleans_2009/GII.4_Sydney_2012 was first detected in Victoria, Australia, in August 2015 at low frequency, and then re-emerged in June 2016, having undergone genetic changes. Analysis of 14 years’ surveillance data from Victoria suggests a typical delay of two to seven months between first detection of a new variant and occurrence of a subsequent epidemic linked to that variant. We consider that the current recombinant strain has the potential to become a pandemic variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…Not surprisingly, there was more sequence variability among GII.4 viruses harboring the GII.Pe and GII.P4 New Orleans polymerases in this study which have been circulating much longer than viruses with the GII.P16 polymerase. Taken together, the three GII.4 Sydney viruses identified in our study appear to be antigenically similar, in contrast with findings reported elsewhere (39). If these in silico findings are bona fide and if polymerase switching occurs without significant antigenic variation, vaccine development efforts may become more complicated.…”
Section: Discussioncontrasting
confidence: 55%
“…Not surprisingly, there was more sequence variability among GII.4 viruses harboring the GII.Pe and GII.P4 New Orleans polymerases in this study which have been circulating much longer than viruses with the GII.P16 polymerase. Taken together, the three GII.4 Sydney viruses identified in our study appear to be antigenically similar, in contrast with findings reported elsewhere (39). If these in silico findings are bona fide and if polymerase switching occurs without significant antigenic variation, vaccine development efforts may become more complicated.…”
Section: Discussioncontrasting
confidence: 55%
“…A comparison of the 2017 strains of the GII.P4_NewOrleans_2009/GII.4_Sydney_2012 recombinant with the previously reported “Melb2016” strain (Figure ) indicated that there were two subsequent variants of the recombinant. The original recombinant “Melb2016” strain and an early 2017 strain of the recombinant (the “intermediate” strain) were transient, with the emergence of a further altered strain first appearing in March 2017 (the “epidemic” strain). This epidemic strain was associated with the majority of norovirus positive outbreaks from May onwards.…”
Section: Resultsmentioning
confidence: 76%
“…Seasonality data (Figure ) showed that 2017 has had a distinctive peak in norovirus outbreaks, with a sharp rise occurring in May followed by 2 months of high norovirus activity, and a decline beginning in August. Sequence analysis of strains in this study has demonstrated that this peak was primarily due to the recombinant GII.P4_NewOrleans_2009/GII.4_Sydney_2012, the epidemic potential of which was first identified in 2016; however, this “Melb2016” strain has since undergone changes.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations